Medicinal plants utilized in the management of epilepsy in Ethiopia: ethnobotany, pharmacology and phytochemistry - Yihenew Simegniew Birhan (BMC, 2022)
Abstract Epilepsy is a common central nervous system (CNS) disorder that affects 50 million people worldwide. Patients with status epilepticus (SE) suffer from devastating comorbidities and a high incidence of mortalities. Antiepileptic drugs (AEDs) are the mainstream treatment options for the symptomatic relief of epilepsy. The incidence of refractory epilepsy and the dose-dependent neurotoxicity of AEDs such as fatigue, cognitive impairment, dizziness, attention-deficit behavior, and other side effects are the major bottlenecks in epilepsy treatment. In low- and middle-income countries (LMICs), epilepsy patients failed to adhere to the AEDs regimens and consider other options such as complementary and alternative medicines (CAMs) to relieve pain due to status epilepticus (SE). Plant-based CAMs are widely employed for the treatment of epilepsy across the globe including Ethiopia. The current review documented around 96 plant species (PS) that are often used for the treatment of epilepsy in Ethiopia. It also described the in vivo anticonvulsant activities and toxicity profiles of the antiepileptic medicinal plants (MPs). Moreover, the phytochemical constituents of MPs with profound anticonvulsant effects were also assessed. The result reiterated that a lot has to be done to show the association between herbal-based epilepsy treatment and in vivo pharmacological activities of MPs regarding their mechanism of action (MOA), toxicity profiles, and bioactive constituents so that they can advance into the clinics and serve as a treatment option for epilepsy.